1990
DOI: 10.1023/a:1015827624296
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The influence of sodium taurocholate (TC) on the intestinal absorption of drugs was studied in vivo in a chronically isolated internal loop in the rat. The hydrophilic drugs paracetamol (PA) and theophylline (TP) and the lipophilic drugs griseofulvin (GF) and ketoconazole (KE) were used as model drugs. The drug concentrations were kept below the saturation concentration. Absorption kinetics of the drugs were evaluated on the basis of disappearance rates of the drug from luminal solutions in the intestinal loop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1992
1992
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…However, the micellar solubilization which gives rise to this important apparent solubility enhancement also results in decreased free fraction of drug. Similar to the case of cyclodextrins, this incorporation of drug in micelles significantly decreases the amount of free drug available for permeation through the intestinal membrane (31,32,34,35,(40)(41)(42).…”
Section: S-p Interplay From Surfactant-based Systemsmentioning
confidence: 93%
See 2 more Smart Citations
“…However, the micellar solubilization which gives rise to this important apparent solubility enhancement also results in decreased free fraction of drug. Similar to the case of cyclodextrins, this incorporation of drug in micelles significantly decreases the amount of free drug available for permeation through the intestinal membrane (31,32,34,35,(40)(41)(42).…”
Section: S-p Interplay From Surfactant-based Systemsmentioning
confidence: 93%
“…Previous studies have shown that the use of surfactants may lead to increased, decreased, or unchanged membrane permeability (31)(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42). It is important to note that surfactants may increase intestinal membrane permeability for drugs with inherently low-permeability and high aqueous solubility (i.e., BCS class III compounds), e.g., through the disruption of membrane integrity to increase paracellular transport (e.g., tight junction opening, which may induce potentially toxic effects) and/or the inhibition of efflux transporters (36,39,(42)(43)(44)(45).…”
Section: S-p Interplay From Surfactant-based Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Situ Rat P e r f u s i o e M a l e Sprague-Dawley rats from Charles River Breeding Laboratories (Wilmington, MA), weighing 300-350 g, were fasted overnight (16)(17)(18)(19)(20) h) prior to inducing anesthesia by im injection of 1.5 g k g body weight of urethane (ethyl carbamate; Sigma). Following anesthesia, rats were put on a heating pad and under a heating lamp to maintain body temperature.…”
Section: Methodsmentioning
confidence: 99%
“…The effect of bile salts on the intestinal absorption of model hydrophilic (paracetamol and theophylline) and lipophilic drugs (griseofulvin, ketaconazole, and dantrolene) was studied by Poelma et al 96,97 using a rat in situ intestinal perfusion technique. Simple or mixed bile salt micelles had no effect on absorption of the hydrophilic drugs, leading to the conclusion that bile salt micelles had minimal effect on the intrinsic barrier function of either the UWL or the intestinal membrane.…”
Section: Absorption Permeability and The Postprandial Intestinementioning
confidence: 99%